Influence of pulse repetition rate on morphology and material removal rate of ultrafast laser ablated metallic surfaces. (May 2019) - Sedao, X.; Lenci, M.; Rudenko, A.; Faure, N.; Pascale-Hamri, A.; Colombier, J.P.; Mauclair, C.
Highlights: The removal rate and surface roughness of ultrafast laser machining of metallic materials (Ni, Cu, stainless steel 316L and Ti-based alloy TA6V) are investigated, for a large range of fluences and repetition rates, by confocal microscopy and differential weighing method. Differential weighing shows that the removal rate per pulse (RRp) is constant regardless of the repetition rate on all metals, contrary to the confocal microscopy depth measurements that underestimates RRp in the case of rugged surfaces. Ni and Cu show a low roughness (Ra below 0.5 µm) at all irradiation conditions whereas stainless steel and Ti-based alloy surface roughness degrades rapidly for high fluences and repetition rates. In this latter case, micro structural analysis (FIB + SEM) reveals that a 10–20 µm re-solidified porous and rugged layer is formed with the presence of spikes, subsurface voids and various grain sizes. The higher roughness obtained on stainless steel and Ti-based alloy is due to a stronger thermal energy confinement because of a lower penetration depth and a longer plasma cooling time, whereas the formation of capillary waves is presumably not possible. Abstract: Ultrafast laser ablation is an efficient method for precise micro-machining. Thanks to the recent development of high repetition rate ultrafast lasers, high speed laser scanning of surfaces is more and more employed to generate micro-/nano- surface structures on metals for a vast variety of applications. Issues associated with these lasers are also identified in micro-machining practice. It is commonly believed that, due to possible shielding effects, the conditions of high fluences and high repetition rates compromise an efficient material removal. However, in this study, based on topography and differential weighing evaluations, we report that the material removal rate holds constant even in sub-MHz regime, up to about 20 J/cm 2 . The morphology of the post-irradiated surface is found to be determined not only by laser processing conditions but also by the material properties on the other hand. Two trends are experimentally identified in surface laser ablation of Ni, Cu, titanium alloy TA6V and stainless steel 316L: while the former two show a low roughness (Ra below 0.5 µm) at all irradiation conditions, the machining quality of the two later ones degrades rapidly with increasing fluences and repetition rates. In such a scenario, a rugged surface layer of 10–20 µm thickness is formed with the presence of numerous subsurface voids. Microstructural analysis is carried out in order to infer physical transition involved in the micro-machining process. Possible mechanisms accounting for the observation are discussed, especially those related to the electron-phonon coupling, plasma dwelling, and capillary waves. These insights pave the way for tailored, material dependent optimizations of ultrafast laser micro-machining processes.